The History of Establishment of Translation Studies as an Interdisciplinary Science - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (Видавничий дім «Гельветика», 2020)
Abstract. The article presents a historical overview of researches that resulted in the emergence of translation studies that has by now incorporated the subject matter of a wide range of disciplines. The first studies of translation dealt with religious and belles-lettres texts. Naturally, the literary theory of translation was the first to be developed by scholars. 1930s marked the start of researches in the field of translating special texts that were not related to religion or fiction. The next direction of translation studies was the linguistic one and was based on equivalence theory. In the course of time it became clear that the linguistic approach has its own limitations. The next paradigm some linguists, like Yves Gambier and Anthony Pym single out is the Internet format due to the digital environment in which translation is performed. We do not agree with this point of view as far as the new technical conditions do not justify a new approach to be distinguished. It seems logical to single out the functionalist approach as the successor of the linguistic one. Translation is regarded as an integral part of a communicative situation; therefore all the parameters of the latter are taken into account in the process of rendering a source text into a target text by means of the instruments of the target language. In 1980s linguists started researching the effect of culture on translation and vice versa. They found the influence so significant that they suggested singling out new approaches: transcreation, transadaptation, and transculturation. However, they fail to recognize that what these new terms refer to has long been known in translation studies as pragmatic or cultural adaptation. At the beginning of the XXI century researchers elaborated an integrative (or interdisciplinary) approach to translation and distinguished three possible views on its character.

Резюме. У статті подано історичний огляд досліджень, які спричинилися до появи перекладознавства, яке на цей час включає проблематику цілої низки дисциплін. Перші наукові розвідки перекладознавства були присвячені аналізу релігійних та художніх текстів. Природньо, що саме літературну теорію перекладу дослідники розробили першою. У 1930х роках з’явилися перші роботи у галузі перекладу спеціальних текстів, які не належали до релігійного жанру або художнього стилю. Наступним напрямом дослідження перекладознавства був лінгвістичний, який базується на теорії еквівалентності. Згодом стало зрозумілим, що мовознавчий напрям має свої обмеження. Наступною науковою парадигмою, яку виділяють вчені, зокрема Ів Гамб’є та Ентоні Пім, є Інтернет формат через цифрове оточення, у якому виконується переклад. Ми не погоджуємося з цією точкою зору, оскільки нові технічні умови не виправдовують виділення нового підходу. Нам видається логічним виділити комунікативно-функціональний підхід, який приходить на зміну / або доповнює лінгвістичний. Переклад вважається невід’ємною частиною комунікативної ситуації; відповідно, беруться до уваги всі параметри останньої під час переведення оригіналу у текст перекладу інструментами цільової мови. У 1980х роках мовознавці почали вивчати вплив культури на переклад та вплив перекладу на культуру цільової мови. Вплив виявився настільки потужним, що було запропоновано виділити нові підходи:транскреацію, трансадаптацію і транскультурацію. Проте, ми не можемо погодитися з цією думкою, оскільки ці нові терміни позначають те, що у перекладознавстві вже давно відомо під назвою прагматична або культурна адаптація. На початку XXI століття лінгвісти розробили інтегративний (також відомий як міждисциплінарний) підхід до перекладу й виділили три можливі погляди на його характер.
Історія становлення перекладознавства як міждисциплінарної науки
Keywords: translation studies; literary theory of translation; linguistic approach to translation; functionalist approach; transcreation; transadaptation; transculturation; interdisciplinary approach